Pengaruh Kualitas Produk, Persepsi Harga, dan Brand Image Terhadap Minat Beli Serum Skincare Hanasui: Studi pada Mahasiswa di Kabupaten Bogor - Agnanisa; Afif Zaerofi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to determine how much influence the variables of product quality, price perception, and brand image have on buying interest in Hanasui skincare serum. Using a quantitative approach with Multiple Linear Regression analysis techniques. Sampling using purposive sampling by distributing questionnaires online via Google Form to 100 students in Bogor district who use / are interested in buying Hanasui skincare serum. The findings of this study provide the results that (1) the product quality variable has a positive and significant effect on buying interest in Hanasui skincare serum for students in Bogor district. (2) the price perception variable has a positive and significant effect on buying interest in Hanasui skincare serum for students in Bogor district. (3) brand image variables have a negative and insignificant effect on buying interest in Hanasui skincare serum among students in Bogor district. Each variable simultaneously has a significant positive effect on buying interest in Hanasui skincare serum among students in Bogor district.